2007
DOI: 10.1111/j.1349-7006.2007.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of caveolin‐1 in a human melanoma cell line results in dispersion of ganglioside GD3 from lipid rafts and alteration of leading edges, leading to attenuation of malignant properties

Abstract: Caveolin-1 is a component of lipid rafts, and is considered to be a tumor suppressor molecule. However, the mechanisms by which caveolin-1 functions in cancer cells are not well understood. We generated caveolin-1 transfectant cells (Cav-1 + cells) using a human melanoma cell line (SK-MEL-28) and investigated the effects of caveolin-1 overexpression on the GD3-mediated malignant properties of melanomas. Cav-1 + cells had decreased cell growth and motility, and reduced phosphorylation levels of p130Cas and paxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 53 publications
5
35
0
Order By: Relevance
“…(34) Recent progress in the isolation and manipulation of glycosyltransferase cDNA enabled us to investigate the roles of these gangliosides in cancer phenotypes. (35) Since we cloned cDNA of GD3 synthase, (13) we have investigated roles of GD3 synthase in melanomas (25,27,31,36,37) and in small-cell lung carcinomas. (38,39) Consequently, it has been demonstrated that the melanoma-specific ganglioside GD3 plays crucial roles in increased proliferation, enhanced invasion and cell adhesion in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(34) Recent progress in the isolation and manipulation of glycosyltransferase cDNA enabled us to investigate the roles of these gangliosides in cancer phenotypes. (35) Since we cloned cDNA of GD3 synthase, (13) we have investigated roles of GD3 synthase in melanomas (25,27,31,36,37) and in small-cell lung carcinomas. (38,39) Consequently, it has been demonstrated that the melanoma-specific ganglioside GD3 plays crucial roles in increased proliferation, enhanced invasion and cell adhesion in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…(26) The TLC was developed with a solvent system of chloroform:methanol:0.2% CaCl 2 ⁄ water (55:45:10), and bands were detected with resorcinol spray as described previously. (27) Sialidase assay. Sialidase activity was assayed with gangliosides mixture or GM3 as substrates and Triton X-100 as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…In cells expressing caveolin-1, GD3 becomes homogeneously distributed in the membrane, rather than concentrated in specific regions. Hence, caveolin-1 is suggested to function as a tumor suppressor in melanoma cells by disrupting GD3-mediated malignant signaling (Nakashima, Hamamura et al 2007). Alternatively, for a non-cutaneous, retinal melanoma, increased caveolin-1 expression was associated with enhanced malignancy.…”
Section: Caveolin-1 In Melanomamentioning
confidence: 99%
“…Cell proliferation was determined by MTT assay (23). On day 0, cells were seeded in 96-well plates (3,000 cells/well) in medium A.…”
Section: Cell Proliferationmentioning
confidence: 99%
“…We and others showed that GD3 enhances proliferation and invasive activity of melanoma and other cells (19)(20)(21)(22) although the molecular mechanism remains poorly understood. GD3 mediates such functions in membrane microdomains known as lipid rafts where cholesterol and sphingolipids are enriched (23). Lipid rafts are essential for various cellular functions (24).…”
Section: Introductionmentioning
confidence: 99%